Antiageing Performance Evaluation of Recycled Engine Oil Bottom Used in Asphalt Rejuvenation - Miaozhang Yu; Jin Li; Xinzhuang Cui; Dedong Guo; Xinjun Li (Advances in Materials Science and Engineering)
To comprehensively evaluate the antiageing performance of recycled engine oil bottom (REOB) used in asphalt rejuvenation, ageing performance studies were carried out on REOB, REOB-rejuvenated asphalt, and REOB-rejuvenated asphalt mixture. The thin film oven test (TFOT) results of REOB and a professional regenerant, RA5, were compared to verify the ageing resistance of REOB as an asphalt regenerant. The quality and viscosity of REOB-rejuvenated asphalt, RA5-rejuvenated asphalt, and base asphalt were measured after extended TFOT (ageing times for 5 h, 10 h, 15 h, 20 h, and 25 h), and the low-temperature performance of three aged asphalts was evaluated by bending beam rheological tests. The corresponding three kinds of asphalt mixtures were used to design and pave surface layers of a full-scale indoor test road. The long-term fatigue performance of indoor asphalt pavement was investigated by a self-developed rotary accelerated loading test (RALT) system. The results show that when used as an asphalt regenerant, REOB meets the antiageing requirements listed in the technical specification. The short-term (TFOT ageing time less than or equal to 10 h) ageing resistance of REOB-rejuvenated asphalt is better than that of RA5-rejuvenated asphalt but worse than that of base asphalt, whereas the long-term (TFOT ageing time greater than or equal to 15 h) ageing resistance of REOB-rejuvenated asphalt is the worst among the three tested asphalts. After long-term ageing, REOB-rejuvenated asphalt is prone to cracking at low temperatures because of its rapid increase in stiffness and sharp decrease in stress relaxation performance. Increasing temperatures increases the deflection value of asphalt pavement as the number of loading cycles increase. High-temperature ageing significantly aggravates the increase of the deflection value of REOB-rejuvenated asphalt pavement under RALT long-term loading, which makes it most prone to fatigue failure among the three pavements. Therefore, the above test results show that REOB used in asphalt pavement rejuvenation is prone to premature and excessive damage.